Housing conditions and COVID-19 in Barcelona: do they change by gender? - Gloria Perez; Lluís Forcadell-Diez; Alexia Reyes; Catherine Perez; Xavier Bartoll; Carme Borrell (BMC, 2024)
Abstract Background Evidence has linked poor housing conditions to negative health outcomes. However, in urban contexts characterized by social vulnerability and population-level inequalities, the gender perspective is often overlooked, despite evidence showing that housing conditions impact men and women differently in terms of health. This study aimed to describe the association between housing conditions and the prevalence of COVID-19 among men and women in Barcelona, Spain. Methods An observational cross-sectional study was conducted using the 2021 Barcelona Health Survey. The study population consisted of non-institutionalized residents over 14 years of age in Barcelona. The survey was administered to a sample of 3,545 participants during the COVID-19 pandemic, between February 2021 and February 2022. Crude and adjusted prevalence ratios of COVID-19 (aPR), along with 95% confidence intervals (95% CI), were estimated using multivariate Poisson regression models with robust variance. The analysis was stratified by gender. Results A significant gradient was observed across age groups for both men and women, with higher COVID-19 prevalence in younger categories. The prevalence was notably higher among individuals born in low-income countries, particularly for women (aPR 1.62). We also identified a significant association between housing conditions, vulnerability factors, and COVID-19 prevalence in both men and women. Living with four or more cohabitants was associated with higher prevalence (aPR 1.96 for women and 1.89 for men), as was the presence of dampness in the home (aPR 1.34 for women and 1.27 for men). Additionally, energy poverty was significantly associated with higher COVID-19 prevalence in women (aPR 1.36), but not in men. Conclusion This study highlights the association between housing conditions and COVID-19 in Barcelona, with a pronounced impact on young people, women from low-income countries, and women experiencing energy poverty.